Improvement Science is a Partner in Basic and Clinical Research. (March 2020) - Kline, Jaclyn N; Payne, Asha S
A breadth of time, effort, and resources are put into research. Improvement science is an applied science emphasizing rapid-cycle testing to learn about change and produce improvement. Its foundations lie in understanding your system, its parts and their relationships, and the psychology of change, yet the framework of improvement science is analogous to basic research. In basic research you first ask a question, then form a hypothesis based on background research. After testing this hypothesis, a researcher then draws conclusions and shares the results. In improvement science, researchers start the same, with asking a question, and then defining what is considered an improvement. Rapid-cycle tests of change are guided by subject matter experts and the people and processes involved. The data provided from these tests of change allow researchers to show improvement and share results. The success of improvement science is showcased through statistical process control charts, which inform when significant change has occurred. Improvement science can be applied across all fields of medicine; is a natural partner to basic and clinical research, as it plays a vital role in the implementation and adoption of the best evidence.